Gender-Based Teams: Perceptions of team satisfaction and effectiveness among engineering students in the United Arab Emirates - Pasha-Zaidi, N.; Afari, Ernest; Mohammed, J.; Cubero, S.; Shoukry, A.; Sokkary, W. (Tempus Publications, 2015)
© 2015 TEMPUS Publications. The development of teamwork skills is an important aspect of engineering education as the interdisciplinary nature of the industry requires graduates to be able to work professionally with others in a team-based environment. Any miscommunication or obstruction from team members can result in lower team performance, thereby affecting the overall goal of the team. With this in mind, many engineering programs have designed their courses to address the teamwork component in engineering. Engineering design courses in particular often focus on teamwork as an integral part of the course in an effort to prepare the students for their careers. The current study addresses the perceptions of team effectiveness and team satisfaction among students working in same-gender teams on two separate campuses of an engineering university in the United Arab Emirates (UAE). Many universities in the Middle East have gender-segregated campuses to promote education while respecting traditional Islamic norms. While the specific execution may differ, the authors anticipate that the results could be translatable to any team-based engineering course in the region. Based on the current study, female students rated themselves as more effective in their teamwork than male students, while male students were more as satisfied with their teams as a whole than female students. Female students also gave higher scores on peer evaluations than male students. In both cases, however, student assessment of individual team members in the peer evaluation was higher in the intermediate course than in the introductory course. Student interviews provided additional insights regarding team processes in UAE university classrooms. The present study provides an exploratory analysis of team effectiveness and satisfaction in this unique sociocultural environment.